Desain Kreatif Pembuatan Flyer Promosi Anggota TP-PKK Desa Selemak Kecamatan Hamparan Perak - Junaidi, Junaidi; Putra Adithia, Muhammad Khaibar; Lubis, Muhammad Zulkarnain; Satriandi, Satriandi; Sarumaha, Demonius; Simbolon, Herry Yusuf (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
The Creative Design of Promotional Flyers for TP-PKK Members in Selemak Village, Hamparan Perak District aims to enhance community awareness of the programs promoted by TP-PKK. The selection of this theme is based on the lack of information regarding the activities and presence of TP-PKK members in the area. The methodology applied includes needs analysis, visual design, and training for TP-PKK members to create informative and engaging flyers. The findings indicate an increase in community participation in TP-PKK programs, as well as an improvement in members' understanding of promotional techniques. The significance of these results lies in their contribution to strengthening the role of TP-PKK as a community empowerment agent and improving communication between members and the broader community.